A Guide to Resources for Severely Wounded Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) Veterans. - Danielle Carlock (Issues in Science and Technology Librarianship)
Military personnel in Iraq and Afghanistan are surviving wounds in numbers far greater than previous wars. Largely due to advances in body armor and combat medicine as well as the rapidity of evacuation, survivorship is close to ninety percent. However many wounded service members are surviving severe injuries which will require sophisticated, comprehensive, and often lifelong care. The purpose of this article is to identify helpful resources for healthcare professionals, veterans, and their families. [ABSTRACT SUPPLIED BY AUTHOR.]